Design, synthesis, and evaluation of substituted alkylindoles that activate G protein-coupled receptors distinct from the cannabinoid CB1 and CB2 receptors - Kline, Toni; Xu, Cong; Kreitzer, Faith R.; Hurst, Dow P.; Eldeeb, Khalil M.; Wager-Miller, Jim; Olivas, Kathleen; Hepburn, Seon A.; Huffman, John W.; Mackie, Ken; Howlett, Allyn C.; Reggio, Patricia; et al. (European journal of medicinal chemistry, 2023)
The alkylindole (AI), WIN55212-2, modulates the activity of several proteins, including cannabinoid receptors 1 and 2 (CB1R, CB2R), and at least additional G protein-coupled receptor (GPCR) that remains uncharacterized with respect to its molecular identity and pharmacological profile. Evidence suggests that such AI-sensitive GPCRs are expressed by the human kidney cell line HEK293. We synthesized fourteen novel AI analogues and evaluated their activities at AI-sensitive GPCRs using [35S]GTPγS and [3H]WIN55212-2 binding in HEK293 cell membranes, and performed in silico pharmacophore modeling to identify characteristics that favor binding to AI-sensitive GPCRs versus CB1R/CB2R. Compounds 10 and 12 stimulated [35S]GTPγS binding (EC50s = 3.5 and 1.1 nM, respectively), and this response was pertussis toxin-sensitive, indicating that AI-sensitive GPCRs couple to Gi/o proteins. Five AI analogues reliably distinguished two binding sites that correspond to the high and low affinity state of AI-sensitive GPCRs coupled or not to G proteins. In silico pharmacophore modeling suggest 3 characteristics that favor binding to AI-sensitive GPCRs versus CB1R/CB2R: 1) an s-cis orientation of the two aromatic rings in AI analogues, 2) a narrow dihedral angle between the carbonyl group and the indole ring plane [i.e., O-C(carbonyl)-C3-C2] and 3) the presence of a carbonyl oxygen. The substituted alkylindoles reported here represent novel chemical tools to study AI-sensitive GPCRs. [Display omitted] •Few chemical tools are available to study uncharacterized G protein-coupled receptors activated by the cannabinoid agonist, WIN55212-2.•Development of substituted alkylindoles that activate uncharacterized Gi/o protein-coupled receptors expressed by HEK293 cells.•Pharmacophore modeling suggest chemical characteristics that differentiate uncharacterized G protein-coupled receptors and cannabinoid receptors.•Alkylindole-sensitive receptors expressed by HEK293 cells couple to Gi/o proteins and exhibit a distinct pharmacology than cannabinoid receptors.